Buccal Mucosal Metastasis of Renal Cell Carcinoma: A Case Report and Review of Literature - Lavanya M, Lithika; Iyer, Pooja; J, Mathangi; Vijayakumar, Rajeev (International Journal of Clinical Research, 2022)
Background: Intraoral metastasis of RCCs are unusual, especially when it comes to buccal mucosal metastases, which are extremely rare, accounting for less than 1% of metastatic RCC. The buccal mucosal metastatic lesion from RCC poses a challenge in diagnosis and treatment. Due to their scarcity, there doesn’t exist any literature primarily concentrating on them. Case Report: In this work, we describe the case of a 58-year-old man affected and operated on for renal cell cancer, brought to our care for the appearance of a buccal mucosal ulcer. Pathological analysis revealed a metastasis compatible with clear-cell carcinoma. Its renal origin was confirmed by immunohistochemical technique. The patient was evaluated and managed after post multidisciplinary tumor board discussion with palliative radiotherapy for local disease. Conclusion: There should be no hurry in starting treatment for a buccal mucosal lesion, and it should be histopathologically evaluated keeping in mind a differential of metastasis from the distant primary. Multidisciplinary tumor board discussion plays an important role in such rare scenarios.